Matching across space: evidence from Finland - Sanna-Mari Ahtonen (European Regional Science Association (ERSA), 2004)
This paper studies spatial aspects in local labour markets in Finland from the perspective of a matching approach. The monthly data comprise 173 Local Labour Office are as over a 12-year period between January 1991 and August 2002. The basic matching function is extended to account for spatial spill-overs between the local labour markets. The role of population density in the matching process is also examined. According to results, the Finnish local labour markets suffer from a strong congestion effect among job seekers, and spatial spill-overs even strengthen the congestion. An open vacancy is filled much easier than a job seeker is employed. The results show that the matching efficiency is remarkable lower in dense areas than elsewhere, which indicates that mismatch is a problem in the local labour markets with high population density. When taking population density into account, returns to scale in the matching function are constant. Keywords: matching, spatial spill-over, population density, returns to scale, Finland
Keywords: 330; matching; spatialspillover; populationdensity; returns-to-scale